1293Identifying Shared Symptoms and Comorbidities to Inform Risk Reduction Strategies Across Prevalent Neurological disorders. (2nd September 2021) - Nag, Nupur; Lin, Xin; Jelinek, George; Neate, Sandra; Levin, Michele
Abstract: Background: The global burden of neurological disorders continues to grow. Many have a long disease course and symptoms that can impact daily living and reduce quality of life. Common symptoms are reported across neurological disorders, however, have not been assessed in detail. Assessment of shared symptoms and conditions across neurological disorders may provide insight into similar risk reduction and disease management opportunities. Methods: Data from an Australian cohort (n = 192, 091) were analysed. Log-binomial regression assessed shared symptoms and comorbidities in ten pre-defined categories across people with Alzheimer's disease (AD), stroke, motor neuron disease (MND), multiple sclerosis (MS), or Parkinson's disease (PD). Then, to identify sub-categories of symptoms and conditions that were driving the shared associations across disorders. Results: Positive associations shared across neurological disorders were observed for cancers, digestive system, mental health, kidney and urinary, lung and breathing, and other conditions, categories. Bladder and urinary problems, incontinence, fatigue, muscle weakness, depression, and sleep apnoea, were associated with at least 3 of 5 neurological disorders. Conclusions: Six overarching symptoms and condition categories were shared across neurological disorders. Bladder and urinary problems, incontinence, fatigue, muscle weakness, depression, and sleep apnoea were associated across most neurological disorders. Key messages: Shared symptoms and conditions were identified across five neurological disorders. These findings may inform risk prevention and disease management strategies with broad applicability.